2022
DOI: 10.3389/fpls.2022.932926
|View full text |Cite
|
Sign up to set email alerts
|

Integration of small RNA, degradome, and transcriptome sequencing data illustrates the mechanism of low phosphorus adaptation in Camellia oleifera

Abstract: Phosphorus (P) is an indispensable macronutrient for plant growth and development, and it is involved in various cellular biological activities in plants. Camellia oleifera is a unique high-quality woody oil plant that grows in the hills and mountains of southern China. However, the available P content is deficient in southern woodland soil. Until now, few studies focused on the regulatory functions of microRNAs (miRNAs) and their target genes under low inorganic phosphate (Pi) stress. In this study, we integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…On one hand, the first SNP (i.e., ENSVATH01403825:A) is the substitution “T => A” at position −33 relative to the transcription start site of ARF1-204 annotated in the Ensembl Plant database [ 31 ], such as “taaaaaaaaaTATAAAGagga => taaaaaaaaaAATAAAGagga” ( Figure 5 a, Table S1 [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, the first SNP (i.e., ENSVATH01403825:A) is the substitution “T => A” at position −33 relative to the transcription start site of ARF1-204 annotated in the Ensembl Plant database [ 31 ], such as “taaaaaaaaaTATAAAGagga => taaaaaaaaaAATAAAGagga” ( Figure 5 a, Table S1 [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , …”
Section: Resultsmentioning
confidence: 99%
“…We also described the possible effect of increased or decreased expression for another 109 genes from having SNPs in proximal promoters by the hand-curated annotation ( Table S1 ) of 83 original articles and found 173 putative advantages ( Table 1 ) such as fast growing [ 43 ], lateral root formation [ 48 ], inorganic phosphate deficiency stress response [ 52 ], antiviral response [ 59 ], photo-oxidative stress response [ 61 ], food allergenicity [ 83 ], susceptibility to parasites [ 89 ], flowering time [ 92 ], trichome number [ 97 ], plant–environment response [ 105 ], seed mineral concentrations [ 108 ], drought stress response [ 111 ], photosynthetic efficiency [ 113 ], cold tolerance [ 116 ], coenzyme Q10 concentration [ 118 ] and resistance to low-nutrient conditions [ 123 ]. These vital plant traits can vary depending on the proximal promoter SNPs, as observed experimentally in 17 crop species ( Table 1 ) such as Cymbidium goeringii [ 41 ], Triticum turgidum [ 51 ], Camellia oleifera [ 52 ], Solanum lycopersicum [ 57 ], Vitis vinifera L. [ 58 ], Oryza sativa L. [ 59 ], Carica papaya [ 60 ], Betula pendula [ 69 ] and Lilium longiflorum [ 72 ] ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This adaptation process has been involved in related gene expression of P uptake and the regulation of transcriptional factors in roots. For example, a recent research on post-transcriptional regulation of microRNA expression in roots under low-P stress in C. oleifera indicated that WRKY53 was one of the three hub transcriptional factors, which were the targets of differentially expressed mRNAs ( Chen et al., 2022 ). However, some researches suggested efficient re-translocation and re-use of the stored P were more important in the breeding or biotechnology of P-efficient varieties, such as the translocation from absorbed P metabolically inactive shoots to active leaves or fruits, or the carbon cost balance between the root development and plant biomass ( Wang et al., 2010 ; Zhang et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The oiltea-camellia plants have extraordinary Mn accumulation and toleration abilities, and proper application of nitrogen and potassium could enhance the efficiency of Mn phytoremediation ( Li et al., 2019 ; Yu et al., 2019 ; Yu et al., 2020 ). Based on the analysis of degradome, transcriptome and small RNA data, thirty-two deferentially expressed miRNAs under low inorganic phosphate treatment, and three hub target genes ( ARF22 , SCL6 , and WRKY53 ) controlling transcriptomic regulation of low inorganic phosphate stress tolerance were identified ( Chen et al., 2022a ). More studies on genetics of nitrogen, phosphate, potassium and other nutrients use efficiency are needed for understanding the molecular mechanism and for better breeding and production strategies.…”
Section: Genes For Abiotic Stress Tolerance and Biotic Stress Resistancementioning
confidence: 99%